Shear Wave Splitting Analysis to Estimate Fracture Orientation and Frequency Dependent Anisotropy - Gholami, Raoof; Moradzadeh, A.; Rasouli, V.; Hanachi, J. (Polska Akademia Nauk * Instytut Geofizyki, 2016)
Shear wave splitting is a well-known method for indication of orientation, radius, and length of fractures in subsurface layers. In this paper, a three component near offset VSP data acquired from a fractured sandstone reservoir in southern part of Iran was used to analyse shear wave splitting and frequency-dependent anisotropy assessment. Polarization angle obtained by performing rotation on radial and transverse components of VSP data was used to determine the direction of polarization of fast shear wave which corresponds to direction of fractures. It was shown that correct implementation of shear wave splitting analysis can be used for determination of fracture direction. During frequency- dependent anisotropy analysis, it was found that the time delays in shear- waves decrease as the frequency increases. It was clearly demonstrated throughout this study that anisotropy may have an inverse relationship with frequency. The analysis presented in this paper complements the studied conducted by other researchers in this field of research.